Integrasi Isu Sosial Lewat Media Digital dalam Pembelajaran Sosiologi Kelas XII - Jesslyn Putri Marella; Diandra Mayla Valiza; Nailal Ghinna; Suyuti Suyuti (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The Society 5.0 era urges the transformation of sociology learning in senior high school (Grade XII) to become more adaptive to current social issues through digital media. This study aims to analyze strategies for integrating social issues via digital approaches and how these affect students’ understanding and participation. Using a qualitative descriptive method, data were collected through classroom observations, semi-structured interviews, and document analysis. Findings indicate that a combination of Learning Management Systems (LMS), gamification, digital collaboration (Padlet, Lumio), and social media significantly increases student engagement, up to 30%, especially in understanding issues such as urbanization, social inequality, and environmental degradation. Interactions among teachers, students, and digital content were actively formed in a virtual environment. However, challenges persist, including limited infrastructure, teachers’ digital literacy, students’ learning discipline, and the lack of local contextualization in teaching materials. This study highlights the importance of synergy between technology, pedagogy, and social sensitivity in issue-based digital learning.